User Adaptation to Satellite Internet in Indonesian Archipelagic Regions: A Qualitative Case Study - M. Haikal Ramadhan; Gunawan Wibisono (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2026)
Archipelagic regions often experience limited telecommunications infrastructure, resulting in unequal Internet access and persistent digital connectivity challenges. Satellite Internet has emerged as a potential solution for expanding broadband access in geographically isolated areas. This study explores user adaptation to satellite Internet technology in the Riau Islands Province, Indonesia. A qualitative case study approach was employed using in-depth interviews, field observations, and documentation involving four active Starlink users selected through purposive sampling. The findings indicate that participants adopted satellite Internet because conventional terrestrial networks could not provide reliable connectivity. Following adoption, users gradually integrated the technology into their daily activities while adapting to weather-related disruptions, antenna positioning, and relatively high subscription costs. Four interrelated dimensions of post-adoption adaptation emerged from the analysis: technical, social, economic, and functional adaptation. The study contributes by proposing an exploratory user-centered framework that explains post-adoption adaptation to satellite Internet in an archipelagic context and extends the Diffusion of Innovation perspective beyond initial adoption. The findings also provide practical insights for service providers and policymakers seeking to improve digital connectivity and digital inclusion in geographically underserved regions.